Assessment of patient safety perception nurses in health system of Bosnia and Herzegovina in COVID period: Descriptive and cross-sectional study (Journal of Health Sciences, 2022)
Introduction: Patient safety depends on a number of factors such as teamwork, working climate, employee satisfaction, work environment, stress awareness, management perception, and attitude. Nurses have a key role to play in protecting and supporting patients, and their assessment serves as a reliable predictor of overall hospital safety. A positive attitude toward patient safety is associated with a significant reduction in complications. The aim of the study was to analyze the perception of nurses about all aspects of patient safety in relation to the workplace and length of service.Methods: The research included 647 nurses employed in health care institutions at the primary, secondary, and tertiary levels of health care. A descriptive and cross-sectional study included nurses from the Federation of Bosnia and Herzegovina. It was conducted in the period from November to December 2021, during the COVID pandemic. A standardized questionnaire on the perception of patient safety was used – Safety Attitudes Questionnaire – SAQ.Results: The analysis of the examined factors in relation to the workplace of the respondents revealed a statistically significant difference in job satisfaction (p < 0.001), as well as in the safety climate at work in relation to the workplace (p = 0.005), working conditions (p < 0.001), and management perception (p < 0.001). Stress levels showed significant differences regarding working position (p = 0.017), but also through the years of service (p = 0.012). Stress was significantly correlated with teamwork (r = 0.124; p = 0.003), showing that better teamwork will help with stress.Conclusion: The synthesis of concepts that includes patient safety and orientation toward patients should be implemented as a strategic quality orientation and set as a priority of every health care system.